The Phenomemon of Blindness and the Movement of Hand - Baranova, Jūratė (Problemos, 2008)
In this article was made an attempt to discuss the interconnections between visuality and the movements of a body (hand) using the reflection of the phenomenon of blindness in the history of philosophy. We considered as a rather informative example of a postmodern “turn towards vision” tranformance of the Cartesian hypotheses concerning the parallel between vision and the movements of the hands of the blind in the book of Jacques Derrida (1930-2004) Memoirs of the Blind: The Self Portrait and Other Ruins (Memoires d’aveugle: L ’autoportrait et autres mins, 1990). The supposed idea of Descartes, that blind man sees with his hand invokes as phenomenological, as deconstructive response in the philosophy of the 20th century. Merleau-Ponty opposes the hypothesis of Descartes about the possible second eyes in the consciousness of the seer, which indicate towards the possibility of the thought creating the image. Trying to negate the rational sources of emergency of a vision Merleau-Ponty stresses pretheoretical, pre-reflective, intuitive genesis of it. On the other hand, opposing Descartes supposed external relation between subject and object, Merleau Ponty stresses more close and interrelated being in the world of sentient body. This supposition of body as a medium between of relation the subject and the word is stressed by Merleau-Ponty using a parallel between seeing and touching as well. Derrida meditates upon the insights of Merleau-Ponty, stressing the possibility of absolute invisibility, discernable in his texts. Derrida divides two aspects of this absolute invisibility: transcendental and sacrificial. We consider, that strategy of arguments suggested by Derrida is more clear as viewed from the perspective of his common practice of deconstructive reading of texts, symbols or culture, in which merges peculiar interchanged tissue of the religious dimension, plots of Bibles, the experience of personal life, even dreams, conceptual modes of meaning coming from other texts of Derrida (in this case – the problem of sacrifice), the experience of reading other philosophical and literary texts. In comparison with other two mentioned philosophers, Derrida meditates the movements of the hands of a blind men totally from the perspective of the “turn towards vision”, all mentioned strategies in writing circles around the represented phenomenon of blindness as expressed in the works of the graphic art. Merleau-Ponty and Derrida, in difference from Descartes for the meditation upon the parallel between the seeing and the movements of hand used the visual art (Merleau-Ponty – works with a colour; Derrida - graphics). Hypothesis of Derrida, concluding, that the drawing of blind man is made by a blind man opens new possibilities for the further reflections upon inner phenomenology of visual art.